Inflammation and psychosocial factors mediate exercise effects on sleep quality in breast cancer survivors: pilot randomized controlled trial. Issue 3 (11th June 2014) - Rogers, Laura Q.; Fogleman, Amanda; Trammell, Rita; Hopkins‐Price, Patricia; Spenner, Allison; Vicari, Sandra; Rao, Krishna; Courneya, Kerry S.; Hoelzer, Karen; Robbs, Randall; Verhulst, Steven
Abstract Objective To improve mechanistic understanding, this pilot randomized controlled trial examined mediators of an exercise intervention effects on sleep in breast cancer survivors (BCS). Methods Forty‐six postmenopausal BCS (≤Stage II, off primary treatment) were randomized to a 3‐month exercise intervention or control group. Intervention included 160 min/week of moderate intensity aerobic walking, twice weekly resistance training (resistance bands), and six discussion groups (to improve adherence). Blinded assessments at baseline and post‐intervention included sleep disturbance (PSQI and PROMIS®), objective sleep quality (accelerometer), serum cytokines, accelerometer physical activity, cardiorespiratory fitness, body composition, fatigue, and psychosocial factors. Mediation was tested using Freedman–Schatzkin difference‐in‐coefficients tests. Results When compared with control, the intervention group demonstrated a significant increase in PSQI sleep duration (i.e., fewer hours of sleep/night) (d = 0.73, p = .03). Medium to large but non‐significant standardized effect sizes were noted for PSQI daytime somnolence (d = −0.63, p = .05) and accelerometer latency (d = −0.49, p = .14). No statistically significant mediators were detected for PSQI sleep duration score or accelerometer latency. Daytime somnolence was mediated by tumor necrosis factor‐alpha (mediated 23% of intervention effect, p < .05), interleukin (IL)‐6:IL‐10 (16%, p < .01), IL‐8:IL‐10 (26%, p < .01), and fatigue (38%, p < .05). Mediating or enhancing relationships for several of the sleep outcomes were noted for accelerometer physical activity, PROMIS® fatigue, exercise social support, and/or physical activity enjoyment. Conclusions Inflammation and psychosocial factors may mediate or enhance sleep response to our exercise intervention. Further study is warranted to confirm our results and translate our findings into more effective interventions aimed at improving sleep quality in BCS. Copyright © 2014 John Wiley & Sons, Ltd.